Practical Guide to Salesforce Communities Building, Enhancing, and Managing an Online Community with Salesforce Community Cloud - Weinmeister, Philip (Apress, 2018)
Whether you are brand new to the world of Salesforce communities or you are looking to take your Community Cloud knowledge to the next level, this detailed guide will help you to build and manage a Salesforce community by leveraging the declarative power of the platform with clicks, not code. Each Salesforce community is a part of a widespread ecosystem, with thousands of communities and millions of users active today on Community Cloud. Through valuable social and business tools, this online platform enables companies to empower and equip their customers, partners, and employees in new, powerful ways. In this book, Philip Weinmeister, a Salesforce MVP and the first-ever recipient of the "Community Cloud MVP" Trailblazer award, leads you through the ins and outs of Salesforce communities and provides you with an array of best practices to deliver top-notch business portals on the Salesforce platform. Practical Guide to Salesforce Communities is the first book to comprehensively cover this next-generation offering from Salesforce, providing real, actionable guidance to help individuals build effective and engaging online communities. The book takes you through the entire process: from planning and designing a community to configuration/build, setup, and administration, all the way to deployment. Detailed explanations are provided of key components, templates, and features such as Community Builder, Audience Targeting, Lightning Bolts, and much more. Additionally, considerations and best practices are covered, including valuable tips and insights. What You'll Learn: Plan and design a community Conceptualize how employees, partners, and customers use and benefit from communities Assess available templates and make an informed selection decision Use Community Builder and Lightning components within a Lightning community template Apply topics and knowledge articles to a community to increase value and adoption Inject process automation into a community using Workflow, Flow, and Process Builder Create dynamic and personalized user experiences with audience targeting Build, export, and import unique templates with the Lightning Bolt solution framework Provide community data for members or community managers.